1995
DOI: 10.1046/j.1471-4159.1995.65020590.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Arginine Transport and Nitric Oxide Production by Lipopolysaccharide Is Mediated by Different Signaling Pathways in Astrocytes

Abstract: Transport of l‐arginine and generation of nitrite in microglia‐free astroglial cultures derived from neonatal mouse brain were stimulated by bacterial lipopolysaccharide (LPS) in a time‐ and dose‐dependent manner. LPS stimulated arginine transport between 1.3‐ and 2.5‐fold; half‐maximal stimulation was obtained with 0.3 µg/ml LPS. Acceleration of transport was detectable within 6 h of incubation with LPS. Cycloheximide or actinomycin D neutralized the effect of LPS. Stimulation of generation of nitrite was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In this study, inhibition of iNOS activity by AMT partially prevented LPS-mediated increase in transport activity (see also Ref. 35). As indicated by Cat1 mRNA levels, there was no modification in Cat1 expression in LPS-treated cells (see also Ref.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, inhibition of iNOS activity by AMT partially prevented LPS-mediated increase in transport activity (see also Ref. 35). As indicated by Cat1 mRNA levels, there was no modification in Cat1 expression in LPS-treated cells (see also Ref.…”
Section: Discussionsupporting
confidence: 58%
“…Controls were carried out using degraded ONOO Ϫ . In some experiments, neurons were depleted of L-arginine by incubating these cells in DMEM containing arginase (2 units/ml; Sigma) for 24 h as described previously (35) before the co-incubation with astrocytes.…”
mentioning
confidence: 99%
“…In cultured astroglial cells, bacterial LPS and IFNÁ induce NO synthesis and stimulate transport of arginine up to severalfold [Simmons and Murphy, 1992;Schmidlin and Wiesinger, 1995]. Therefore, the effect of preincubation of the astroglia-rich primary cultures with immunostimulants was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, an intracellular NO/citrulline cycle within astroglial cells should not be ruled out. In contrast to up-regulation of glial arginine synthesis [Heneka et al, 1999;Schmidlin and Wiesinger, 1998] and arginine transport [Schmidlin et al, 1995] by immunostimulants, uptake of citrulline by glial cells does not respond to compounds such as LPS or IFNÁ, strong inductors of NO synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…In different cells including MΦ and AMΦ it has been observed that stimuli which induce iNOS, i.e. cause an enhanced demand of L-arginine, also increase L-arginine uptake (Bogle et al 1992;Sato et al 1992;Lind et al 1993;Schmidlin and Wiesinger 1995;Mössner et al 1998). …”
Section: Maria Donata Messeri Dreißig · Rainer Hammermann · Jutta Mösmentioning
confidence: 99%